Hubungan Kualitas Kehidupan Kerja, Kepuasan Kerja, dan Integritas Akuntan Publik - Mila Hariani; Ella Anastasya Sinambela (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The development of the accounting profession, especially public accountants in a country, goes hand in hand with the development of business in that country. This profession has the responsibility to improve the level of financial reporting performance. More attention should be paid to the accounting profession. The same applies to their work behavior. This descriptive and correlational study examines the relationship between the perceived quality of work life of public accountants and job satisfaction and integrity. The analysis tool is correlation and assisted by SPSS. The findings mention the relationship between quality of work life and job satisfaction found a significant and positive linear relationship. Improving the quality of work life results in increased job satisfaction. In addition, the relationship between quality of work life and integrity shows an insignificant and positive linear relationship between the two variables. Likewise, the relationship between job satisfaction and integrity was not found to have a significant relationship